2003
DOI: 10.2188/jea.13.15
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Fatty Liver and Diabetes Risk.

Abstract: We examined whether fatty liver, as diagnosed with abdominal ultrasonography , is an independent risk factor for diabetes mellitus during 10 years of follow-up . A total of 840 subjects (467 men and 373 women) were followed for the entire 10 years. The criteria for being non-diabetic were having no history of diabetes, having a fasting plasma glucose level of less than 110 mg/dl and a serum hemoglobin Air level of 6.4% or less. We indicated that every examine received all examinations after 12 hours of fasting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 25 publications
2
41
1
2
Order By: Relevance
“…Two longitudinal studies in Asian populations using ultrasound (US)-diagnosed NAFLD have demonstrated that NAFLD is a risk factor for the development of type 2 diabetes in Koreans [7] and Japanese men [8]. In contrast, a study in a Japanese cohort that included women [9] failed to show this relationship. Hence, the emergence of NAFLD prior to the development of frank diabetes is not well studied in women.…”
Section: Introductionmentioning
confidence: 99%
“…Two longitudinal studies in Asian populations using ultrasound (US)-diagnosed NAFLD have demonstrated that NAFLD is a risk factor for the development of type 2 diabetes in Koreans [7] and Japanese men [8]. In contrast, a study in a Japanese cohort that included women [9] failed to show this relationship. Hence, the emergence of NAFLD prior to the development of frank diabetes is not well studied in women.…”
Section: Introductionmentioning
confidence: 99%
“…There are now about 20 observational studies that have assessed the association between NAFLD and the risk of new-onset type 2 diabetes [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Epidemiological Evidence Linking Nafld To the Risk Of New-onmentioning
confidence: 99%
“…Amongst these published studies, nearly all (except for the study by Okamoto et al [9]) have shown that NAFLD was associated with a substantially increased risk of new-onset type 2 diabetes. The risk of diabetes among these published studies varied markedly from a 33% increase [14] to a 5.5 fold increase in risk [11].…”
Section: Epidemiological Evidence Linking Nafld To the Risk Of New-onmentioning
confidence: 99%
See 1 more Smart Citation
“…REVIEW 340 | Сахарный диабет / Diabetes Mellitus талось, что они являются просто структурными клеточны-ми компонентами, однако в настоящее время появились данные о том, что избыток мембранных церамидов может способствовать развитию ИР [27] ввиду того, что церами-ды имеют функцию клеточного сигналинга, потенциально обеспечивая механизм связи печеночного метаболизма липидов и печеночного воспаления. Не так давно пред-полагалось, что изменения в метаболизме церамидов мо-гут также объяснять, почему НАЖБП с ИР ассоциирована с другими характерными признаками метаболического синдрома, в то время как генотип пататин-подобного доме-на, содержащего протеин 3 фосфолипазу (PNPLA3 148MM), ассоциированный с НАЖБП, не связан с метаболическим синдромом (и не связан с повышенным риском развития СД2) [28]. В данном исследовании оценивался печеноч-ный липидом на основании 125 биопсий, пациенты были разделены по двум признакам: ИР (оценка проводилась по уровню HOMA) и генотипу PNPLA3 (PNPLA3 148MM/MI и PNPLA3 148II).…”
Section: инсулинорезистентность и нажбпunclassified